Real-time kidney graft perfusion monitoring using infrared imaging during pediatric kidney transplantation. Issue 3 (May 2019) - Fernandez, N.; Lorenzo, A.; Chua, M.; Koyle, M.A.; Farhat, W.; Matava, C.
Summary: Introduction: Ischemia times in kidney transplantation have shown to be predictive for future graft function. Preservation solutions and anticoagulation protocols have improved the management of pediatric kidney transplantation. Nonetheless, there is no current tool for intra-operative graft monitoring. The aim of this project is to present a novel technique for intra-operative real-time assessment of graft perfusion using a non-invasive infrared camera. Methods: Prospectively, the authors included 10 pediatric patients. Surgical procedure followed their institutional protocol. Infrared imaging was captured at graft preparation, vascular anastomosis, unclamping, and at 30 s, 1, 5, and 10 min after unclamping. Analyzed variables included type of transplant, ischemia and procedure times, type of anastomosis, and results of doppler/ultrasound. Postoperative variables included creatinine levels during first 72 h. Any complications were also recorded. Delta analysis was calculated to establish the variation of temperature after unclamping. Results: Average age at transplant was 9.9 years. Five cases were living donor transplants. Mean overall ischemia time was 395.6 (SD 64.4 min). Two patients had poor graft perfusion after unclamping. Of those, one had torsion of the arterial anastomosis and the other was a graft from a donor that required cardiopulmonary resuscitation for 45 min. Thermal imaging showed a correlation of 0.318 between graft temperature change and creatinine decrease. Cut-off delta for temperature for good reperfusion was above 0.2 at 1 min Conclusion: Real-time infrared imaging shows to be a promising option for non-invasive graft perfusion monitoring. Initial results show good correlation between intra-operative temperature changes, graft perfusion, and postoperative graft function. Summary Fig A) Thermal image of kidney graft after unclamping. (B) Digital reconstruction of the kidney graft after unclamping. Summary Fig